Case of Superficial Cancer Located at the Pharyngoesophageal Junction Which Was Dissected by Endoscopic Laryngopharyngeal Surgery Combined with Endoscopic Submucosal Dissection. (5th January 2017) - Kawada, Kenro; Kawano, Tatsuyuki; Sugimoto, Taro; Yamaguchi, Kazuya; Kawamura, Yuudai; Matsui, Toshihiro; Okuda, Masafumi; Ogo, Taichi; Kume, Yuuichiro; Nakajima, Yutaka; Mora, Andres; Okada, Takuya; et al.
Abstract : Aims . In order to determine the indications of transoral surgery for a tumor located at the pharyngoesophageal junction, the trumpet maneuver with transnasal endoscopy was used. Its efficacy is reported here. Material and Methods . An 88-year-old woman complaining of dysphagia, diagnosed with cervical esophageal cancer, and hoping to preserve her voice and swallowing function was admitted to our hospital. Conventional endoscopy showed that the tumor had invaded the hypopharynx. When inspecting the hypopharynx and the orifice of the esophagus, we asked the patient to blow hard and puff her cheeks with her mouth closed (trumpet maneuver). After the trumpet maneuver, the pharyngeal mucosa was stretched out. The pedicle of the tumor arose from the left-anterior wall of the pharyngoesophageal junction, so we decided to perform endoscopic resection. Result . Under general anesthesia, the curved laryngoscope made it possible to view the whole hypopharynx, including the apex of the piriform sinus and the orifice of the esophagus. The cervical esophageal cancer was pulled up to the hypopharynx. Under collaboration between a head and neck surgeon and an endoscopist, the tumor was resected en bloc by endoscopic laryngopharyngeal surgery combined with endoscopic submucosal dissection. Conclusion . Transnasal endoscopy using the trumpet maneuver is useful for a precise diagnosis of the pharyngoesophageal junction. Close collaboration between head and neck surgeons and endoscopists can provide good results in treating tumors of the pharyngoesophageal junction.